(untitled) (American Journal of Islam and Society, 2001)
Education In The Arab Gulf States And The Arab World: An Annotated Bibliography is divided into six parts. Each part contains between one to ten chapters according to the topic. In the preface, the author mentions that she includes all references found in US libraries and the Library of Congress and does not include references from Arab countries. She also mentions that she was "selective" in her choices of what to include and what not. For example, literature from the social sciences that contained a lot of stereotyping and biased information about Islam, Arabs and Arab society in general was excluded. Unpublished works also were not included. The author then describes her method of listing the bibliography: when there was literature available on the Arab world in general, she included that, and then she would list the seven Gulf States in alphabetical order. If there were no references for a country, then the country is not mentioned and she jumps to the next country in that order. Part One contains only one chapter, which is the introduction. ElSannbary presents an historical overview of the Gulf States, which is her focus: Bahrain, Iraq, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates. A map of the region is presented on page four. She surveys the history and the present conditions of the seven states economically, politically and educationally. The rest of the chapter includes a one-page summary on all the topics, which are mainly the chapters that follow. Part Two comes under the heading "General Background and Resources", and consists of three chapters. Chapter Two, "Context of Education", contains 165 entries. It starts with the Arab World (entry 1-52) followed by Bahrain (52-60), Iraq (61-76), Kuwait (77-95), Oman (96- 102), Qatar (103-108), Saudi Arabia (109-154), and the United Arab Emirates, (155-165). This is the system followed throughout the whole book. When there is no literature available on a country, it is not mentioned. Chapter Three, "Bibliographies and References", starts with general references (166- 215), and then is followed by Iraq (216), Kuwait (217), Oman (218-2190, Qatar (220-223), United Arab Emirates (224) and finally educational references (225-259). Chapter Four, "Religion and Education," lists 120 entries (260-380) ...